On Extended Spectrum of a Composition Operator on Sequence Spaces - Otieno, Dancun; Omoke, Priscah; Bonyo, Job (Annals of Mathematics and Computer Science, 2025)
In this paper, we investigate the spectral properties of a composition operator Cα : ` p → ` p , where 1 ≤ p < ∞ and a null sequence α = (αk)k∈N, defined by Cαx = (0, α1x1, α2x2, . . .). In particular, we prove that the point spectrum, the approximate point spectrum as well as the spectrum of Cα all coincide and is the singleton set containing 0. However, the extended spectrum of Cα turns out to be the complement of the closed unit disc of the complex plane.
Keywords: Extended spectrum; Eigenvalues; Sequence spaces; Composition operator